Cytokine Consistency Between Bone Marrow and Peripheral Blood in Patients With Philadelphia-Negative Myeloproliferative Neoplasms - Chen, Pu; Wu, Boting; Ji, Lili; Zhan, Yanxia; Li, Feng; Cheng, Luya; Cao, Jingjing; Chen, Hehui; Ke, Yang; Min, Zhihui; Sun, Lihua; Hua, Fanli; et al. (Frontiers in Medicine, 2021)
Background Inflammation might play a critical role in the pathogenesis and progression of Philadelphia-negative myeloproliferative neoplasms (Ph-MPNs) with elevated inflammatory cytokines in peripheral blood (PB). However, the inflammatory status inside the bone marrow (BM), which is the place of malignancy origin and important microenvironment of neoplasm evolution, has not yet been elucidated. Methods Inflammatory cytokine profiles in PB and BM of 24 Ph-MPNs patients were measured by a multiplex quantitative inflammation array. Cytokines that correlated between PB and BM were selected and then validated by ELISA in a separate cohort of 52 MPN patients. Furthermore, a panel of cytokines was identified and examined for potential application as non-invasive markers for the diagnosis and prediction of fibrosis progress of MPN subtypes. Results The levels of G-CSF, I-309, IL-1β, IL-1ra, IL-12p40, IL-15, IL-16, M-CSF, MIG, PDGF-BB and TIMP-1 in BM supernatants were significantly higher than those in PB (all p < 0.05). Linear correlations between BM and PB levels were found in 13 cytokines, including BLC, Eotaxin-2, I-309, sICAM-1, IL-15, M-CSF, MIP-1α, MIP-1δ, RANTES, TIMP-1, TIMP-2, sTNFRI and sTNFRII (all R > 0.4 and p < 0.05). Levels of BLC, Eotaxin-2, M-CSF, and TIMP-1in PB were significantly different from those in health controls (all p < 0.05). In PB, levels of TIMP-1 and Eotaxin-2 in essential thrombocythemia (ET) group were significantly lower than those in groups of prefibrotic primary myelofibrosis (pre-PMF) [TIMP-1: 685.2 (322.2-1229) ng/ml vs 1369 (1175-1497) ng/ml, p = 0.0221; Eotaxin-2: 531.4 (317.9-756.6) pg/ml vs 942.4 (699.3-1474) pg/ml, p = 0.0393] and primary myelofibrosis (PMF) [TIMP-1: 685.2 (322.2-1229) ng/ml vs 1365 (1115-1681) ng/ml, p = 0.0043; Eotaxin-2: 531.4 (317.9-756.6) pg/ml vs 1010 (818-1556) pg/ml, p = 0.0030]. The level of TIMP-1 in myelofibrosis (MF) > 1 group was significantly higher than that in MF ≤ 1 group. Conclusion Abnormal inflammatory status is present in MPN, especially in its BM microenvironment. Consistency between PB and BM levels was found in multiple inflammatory cytokines. Circulating cytokine levels of BLC, M-CSF, Eotaxin-2, and TIMP-1 reflected inflammation inside BM niche, suggesting potential diagnostic value for MPN subtypes and prognostic value for fibrosis progression.